Friendship Quality, Loneliness, and Subjective Well-Being among Roma Primary School Children in Türkiye - Erol, Mustafa; Erol, Ahmet (SPRINGER, 2026)
This study examines the relationships between friendship quality, loneliness, and subjective well-being among Roma primary school children in T & uuml;rkiye, who face socio-cultural disadvantages and structural barriers in educational processes. Additionally, the study examines whether loneliness serves as a mediator in the relationship between friendship quality and subjective well-being. A total of 279 Roma children participated, and data were collected using the Friendship Quality Questionnaire (FQQ), the Children's Loneliness Scale (CLS), and the Subjective Well-Being Scale (ESSWBS). The data were analyzed using a general linear mediation (GLM) analysis. The study's findings revealed a positive correlation between subjective well-being and friendship, and a negative correlation between friendship and loneliness. Additionally, a negative relationship between subjective well-being and loneliness was found, and loneliness mediated the relationship between subjective well-being and the quality of friendships. These results highlight the role of friendship as a protective factor for children with novels.
Keywords: Friendship quality; Loneliness; Subjective well-being; Roma children; FIT INDEXES; LIFE SATISFACTION; NEIGHBORHOOD; ACCEPTANCE; CHILDHOOD; SUPPORT; FAMILY; LINKS; Social Sciences - Other Topics